2015
DOI: 10.1177/1465116515584202
|View full text |Cite
|
Sign up to set email alerts
|

Beyond rules and resources: Parliamentary scrutiny of EU policy proposals

Abstract: This article examines the factors that shape parties' motivation to invest time and other resources in scrutinizing European Union policy proposals. We distinguish between two different motivations to engage in scrutiny activities. First, parties use such mechanisms to influence the national position directly. Second, parties play a two-level game and use scrutiny to manipulate their negotiator's domestic constraints. Both arguments depend on a set of conditions, namely the government's relative strength in Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 41 publications
0
19
1
Order By: Relevance
“…The network of national parliament representatives in Brussels, for instance, also played a major role in the coordination of the first yellow card within the EWS (Cooper, 2015), which suggests that they continue to be an indicator for mainstreaming in the dimension of IPC in the future. Thus far, however, we find little evidence for IPC at the party level postLisbon, although research has identified them as key players in EU affairs scrutiny (Finke and Herbel, 2015;Strelkov, 2015) and acknowledges the importance of transnational party networks in the case of Atalanta (Peters et al, 2014: 443).…”
Section: Manifestations Of the Mainstreaming Of Eu Affairs Scrutinymentioning
confidence: 81%
“…The network of national parliament representatives in Brussels, for instance, also played a major role in the coordination of the first yellow card within the EWS (Cooper, 2015), which suggests that they continue to be an indicator for mainstreaming in the dimension of IPC in the future. Thus far, however, we find little evidence for IPC at the party level postLisbon, although research has identified them as key players in EU affairs scrutiny (Finke and Herbel, 2015;Strelkov, 2015) and acknowledges the importance of transnational party networks in the case of Atalanta (Peters et al, 2014: 443).…”
Section: Manifestations Of the Mainstreaming Of Eu Affairs Scrutinymentioning
confidence: 81%
“…Most importantly, this benefits opposition parties that are not directly involved in council negotiations (Finke and Herbel 2015). However, acquiring information is not an end in itself.…”
Section: Parliamentary Scrutiny and Voting Defectionmentioning
confidence: 99%
“…In this article the approach of Finke and Dannwolf (2013) is followed in considering the referral of EU policy proposals to national parliamentary committees a crucial first step of any parliamentary scrutiny process. The author compiled a unique dataset on committee referrals for all European policy proposals from 2000 to 2013 (Finke and Herbel 2015). Information about the composition of parliaments and governments was retrieved from the parlgov.org database (Döring and Manow 2015).…”
Section: Scrutiny and Voting In The Epmentioning
confidence: 99%
“…In addition, they demonstrate that MPs from both opposition and government parties ask questions to the government to scrutinize the minister in charge of EU policy proposals. In a similar vein, Finke and Herbel (2015) compare the scrutiny activities at the level of parliamentary committees in 3 more comprehensive understanding of how MPs mobilize parliamentary instruments and references to the EU to pursue both policy-seeking and vote-seeking strategies.…”
Section: Maurer and Wessels 2001mentioning
confidence: 99%
“…These parties rather tend to focus on a « monitoring scrutiny » (Auel 2007), which consists in asking the Executive to inform, to clarify and to explain its policy strategy. This less intrusive scrutiny may seek to avoid a ministerial drift in EU matters (Navarro andBrouard 2014, Finke andHerbel 2015), to strengthen the bargaining position of the government at the EU level and to protect the government from Eurosceptic parties (Holzhacker 2002: 467). Consequently, the tone of parliamentary interventions introduced by non-Eurosceptic, governmental parties should be neutral or even positive towards the EU.…”
Section: Furthermore Mps From the Swiss People's Party Introduce Mormentioning
confidence: 99%